Prática deliberativa no Conselho Municipal de Saúde de Cascavel PR - Borges, Vânia Venzel (2014)
The research intent to analyze the effectiveness of deliberative perform on Cascavel s Municipal Health Council and find out how the deliberative process occurs (comprehended as discursive process/debate and resolutive one) and also to comprehend how the applicability of equality, plurality and advertise deliberative principles on Cascavel s Municipal Health Council. The study of deliberative practice started from the analysis of regular and special meetings minutes, attendance lists, relationship between counselors and their segments, creating laws, resolutions, bylaw and partaking observation of board meetings during 2012/2013 management. Starting from the comprehention of the limitations derived from social context, political project and the political culture, the study proves the limited Council s power of influence in the definition of local health policy process.